Investigation of enzyme activities of dermatophytes isolated from different clinical samples by ApiZYM method [Çeşitli klinik örneklerden izole edilen dermatofitlerin enzim aktivitelerinin ApiZYM yöntemiyle tayini] - (:unkn) unknown (My University, 2005)
Dermatophytes' enzymes may have a role in chronic superficial infections. In this study it was planned to investigate the possible relationship between the enzymatic activities of the dermatophytes and acute or chronic course of the infections. Dermatophytes were isolated from 58 (72%) out of 81 patients with superficial infections. The infections were divided into two groups as acute (≤6 weeks) or chronic (>6 weeks). Isolated fungi were identified by the classical methods and ApiZYM method. ApiZYM exhibits 19 different enzymatic activities. From 11 acute cases; five Epidermophyton floccosum, three Trichophyton rubrum, two Microsporum canis and one Trichophyton mentagrophytes strains were isolated. Of the 47 chronic cases, 96% was due to T.rubrum and 4% due to T.mentagrophytes. Production of alkaline phosphatase, leucine arylamidase and β-glucosidase enzymes were detected in all tested strains. There was no difference between the enzymatic activities of acute and chronic cases. Alpha-mannosidase activity was detected in all of the species isolated from acute cases whereas none of the chronic cases were positive (P<0.001). The results of this study suggest that α-mannosiclase activity may play a role in both cutaneous inflammatory response caused by dermatophytes and the chronicity of the lesions.
Keywords: ApiZYM; Dermatophytes; Enzymes